Sorbcion-Photometric Determination Of Iron (Ii) Ion In Industrial Waste Of" Olmaliq Kmk "Aj Using Diethyl 2,2'-(1,3,4- Thiadiazole-2,5-Diyl) Bis(Sulfandiyl) Diacetate Organic Reagent (Genius Repository, 2023)
Diethyl 2,2'-(1,3,4-thiadiazole-2,5-diyl) bis (sulfandiyl) diacetate was selected as the organic analytical reagent for the Iron(II) ion contained in the wastewater technological water of industrial and environmental facilities of JSC" Olmaliq KMK". The conditions under which the 2,2 ' -(1,3,4-thiadiazole-2,5-diyl) BIS (sulfandiyl)) diacetate organic reagent immobilizes to carriers with different tolcases have been studied.